Sodium MRI of the Lumbar Intervertebral Discs of the Human Spine: An Ex Vivo Study - Kamp, Benedikt; Radke, Karl Ludger; Knet, Marek; Strunk, Rosanna; Gallinnis, Patrik J.; Nagel, Armin Michael; Filler, Timm J.; Antoch, Gerald; Abrar, Daniel B.; Frenken, Miriam; Wittsack, Hans Jörg; Müller-Lutz, Anja (Journal of Magnetic Resonance Imaging, 2024)
Background: Lower back pain affects 75%–85% of people at some point in their lives. The detection of biochemical changes with sodium (23Na) MRI has potential to enable an earlier and more accurate diagnosis. Purpose: To measure 23Na relaxation times and apparent tissue sodium concentration (aTSC) in ex-vivo intervertebral discs (IVDs), and to investigate the relationship between aTSC and histological Thompson grade. Study Type: Ex-vivo. Specimen: Thirty IVDs from the lumbar spines of 11 human body donors (4 female, 7 male, mean age 86 ± 8 years). Field Strength/Sequence: 3 T; density-adapted 3D radial sequence (DA-3D-RAD). Assessment: IVD 23Na longitudinal (T1), short and long transverse (T2s* and T2l*) relaxation times and the proportion of the short transverse relaxation (ps) were calculated for one IVD per spine sample (11 IVDs). Furthermore, aTSCs were calculated for all IVDs. The degradation of the IVDs was assessed via histological Thompson grading. Statistical Tests: A Kendall Tau correlation (τ) test was performed between the aTSCs and the Thompson grades. The significance level was set to P < 0.05. Results: Mean 23Na relaxation parameters of a subset of 11 IVDs were T1 = 9.8 ± 1.3 msec, T2s* = 0.7 ± 0.1 msec, T2l* = 7.3 ± 1.1 msec, and ps = 32.7 ± 4.0%. A total of 30 IVDs were examined, of which 3 had Thompson grade 1, 4 had grade 2, 5 had grade 3, 5 had grade 4, and 13 had grade 5. The aTSC decreased with increasing degradation, being 274.6 ± 18.9 mM for Thompson grade 1 and 190.5 ± 29.5 mM for Thompson grade 5. The correlation between whole IVD aTSC and Thompson grade was significant and strongly negative (τ = −0.56). Data Conclusion: This study showed a significant correlation between aTSC and degenerative IVD changes. Consequently, aTSC has potential to be useful as an indicator of degenerative spinal changes. Evidence Level: 2. Technical Efficacy: Stage 1.
CRIS-Team Scopus Importer:2024-07-12
Keywords: ex vivo; intervertebral disc; IVD; sodium MRI